I'll aussme has an inverse.
But we all know what happens when we ass/u/me.
This seems right and .
With we have
giving us .
If X is continous with distribution function F(x) and pdf f(x). It is given
Y=2X, finding the distribution of Y will be:
Fy(a)= P(Y< a)
= P(2X< a)
= P(X< a/2)
Differentiation will give me:
fy(a) = 1/2fx(a/2)
What if the relationship is Y= 2 F(X), where F(X) is the cumulative distribution of X. I can't seem to make X the subject of the above equation.
Hey really thanks a lot.
I think the case when really help a lot!
By the way, assuming now X is a continous normal distribution with cumulative density φ(X), will this still work? For example may i use
when in this case, Y= 2φ(X) rather then Y= 2F(x)
Will the answer be still be ??